Beat the Streak - Alceo, Pedro (2022)
Alceo, P., & Henriques, R. (2020). Beat the Streak: Prediction of MLB Base Hits Using Machine Learning. In A. Fred, A. Fred, A. Salgado, D. Aveiro, J. Dietz, J. Bernardino, & J. Filipe (Eds.), Knowledge Discovery, Knowledge Engineering and Knowledge Management: 11th International Joint Conference, IC3K 2019, Revised Selected Papers (pp. 108-133). (Communications in Computer and Information Science; Vol. 1297). Springer Science and Business Media Deutschland GmbH. https://doi.org/10.1007/978-3-030-66196-0_6